Projeto integrador: a educação ambiental como prática interdisciplinar no ensino médio - Nascimento, Alzenir Herley Marques do (2023)
The present research aimed to analyze the contribution of an Integrative Project in the process of teaching Environmental Education content, with emphasis on the Caatinga biome, based on interdisciplinary proposals in line with the National Common Curricular Base. Integrative Projects happen when they bring together more than one discipline, teachers or even area of knowledge, they are projects that articulate various points of view and knowledge, bringing up everyday issues and helping students to understand the connections between school knowledge and the world real. The project had an interdisciplinary character, in which the Biology discipline dialogued with the other components of the Natural Sciences area in High School, that is, Physics and Chemistry. The research took place in a Full-Time High School located in the city of Crateús/CE, semi-arid region of the Caatinga, which justified the emphasis on this biome. As a methodological path, we opted for a narrative of planned experience using semistructured interviews, document search and notes in a logbook as data collection tools. I, as a researcher and School Coordinator, together with three teachers participated as research subjects, the teachers for teaching the subjects of Biology, Physics and Chemistry in the 1st grade classes at that school. The focus of the research was the teachers' perception of developing and implementing an Integrative Project. Data analysis followed the line proposed by objective hermeneutics, a science centered on the interpretation of written protocols. Having said this, it was possible to understand that the use of Integrative Projects worked as a methodology applicable to Natural Sciences content and that interdisciplinarity was the main characteristic developed in the project, although the teachers demonstrated difficulty in preparing the interdisciplinary proposals. Despite the adversities, all teachers agreed that the work favored the contextualized learning of Environmental Education with an emphasis on the Caatinga biome and that the Integrator Project boosted Youth Protagonism.